Study on Maneuvering Target Trajectory Simulation and Tracking Based on IMM algorithm - Ma, J R; Ma, Q H; Yang, S J; Zheng, J Q; Wang, S W (Journal of physics. Conference series, 2023)
On the background of air defense missile which use radar command guidance, this article focuses on the maneuvering target trajectory simulation and tracking problem by considering possible maneuvering modes and target overload. Taking Serpentine maneuvering (S maneuvering) as an example, the target trajectory is simulated based on overload using stepwise design method, and data are measured through sensor models. Since single model cannot model the maneuvering target motion exactly, the estimation is addressed by combining the interacting multiple model algorithm and unscented Kalman filter algorithm, so as to study the applications of maneuvering target trajectory simulation and tracking in air defense missile systems. The effectiveness of the algorithm is demonstrated with simulated data.